Developing reading skills through authentic texts - Berdikulova, А.С.; Kapantaykyzy, Ш. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The reading of the texts should be related to real life, a person, and society. This concept is based on the requirements for texts as a communicative unit. The relevance of the problem is due to the need to choose effective ways to develop the reading skills of the target language. In this regard, the purpose of the article is to consider the possibility of organizing an effective communicative learning process and using authentic textual materials as an effective way of teaching a language. The theoretical part of the article reviews the work of scientists who studied the problem of teaching reading, based on authentic texts, as a means of teaching the language. As a result, the definitions of the concepts of "authenticity" and "authentic materials" in the works of scientists who considered ways to develop reading skills have been explored. The types of authentic texts were analyzed. Aspects of the use of authentic text materials are considered, and the stages of reading organization and types of tasks for each type of text are determined. In the practical part of the study, special attention was paid to the study of authentic information texts, which allow students to expand their vocabulary, learn the basics of an authentic text, and develop vocabulary skills. The issues raised in the article are of practical importance in terms of organizing work with authentic materials in foreign language classes and making a theoretical and practical contribution to the study of authenticity.